A Learning Model of Religious Moderation: Learning from Islamic Schools - Zafi, Ashif Az; Partono, Partono; Kamil, Tasallia Nima (IAIN Ponorogo, 2023)
This study aims to describe the method and evaluation of internalizing religious moderation at school. This research was qualitative and conducted at a senior high school in Purworejo. The researchers obtained the data from observation and interviews involving the students, teachers, vice principal, and headmaster. It investigated the teaching-learning methods and evaluation of the learning process. This study's results showed that four methods were used to internalize the values of religious moderation. They were the cooperation of the school elements, the learning process, strengthening the values in each student's activities, and the other activities, such as field trips. The evaluation of the internalization of religious moderation values in schools can be done through three evaluations. Formulating the four methods and three learning evaluations can be a model for learning religious moderation. Based on the research results, this research contributes to such a way that the school can adapt to internalize the values of religious moderation to the students.